2022
DOI: 10.1021/acs.joc.2c00922
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Synthesis of Fluorescent Thiazole–Indole Hybrids and Thiazole-Based Novel Polymers

Abstract: Herein, we report an efficient multicomponent reaction for the synthesis of trisubstituted thiazoles involving a one-pot C–C, C–N, and C–S bond-forming process from the readily available starting materials. The reaction of arylglyoxal, indole, and aryl thioamides in the acetic acid medium under sealed heating conditions provided 3-(2,4-diarylthiazol-5-yl)-1H-indoles (4) in good to excellent yields. Using a similar reaction strategy, the reaction of arylglyoxal, aryl thioamide, and 2,5-dihydroxy-1,4-benzoquinon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The 1,3-dicarbonyls, [30] indoles [31] are popular precursors in MCRs. In this backdrop, Mitra et al in 2021 reported the humic acid-catalyzed synthesis of a library of molecules under solventfree conditions as shown in Scheme 3.1, 3.2, 3.3 and 3.4.…”
Section: Humic Acid In Condensation and Michael Additionmentioning
confidence: 99%
“…The 1,3-dicarbonyls, [30] indoles [31] are popular precursors in MCRs. In this backdrop, Mitra et al in 2021 reported the humic acid-catalyzed synthesis of a library of molecules under solventfree conditions as shown in Scheme 3.1, 3.2, 3.3 and 3.4.…”
Section: Humic Acid In Condensation and Michael Additionmentioning
confidence: 99%
“…Over the past few decades, the preparation of polysubstituted thiazole skeletons has become particularly interesting, as such skeletons are particularly important N- and S-containing heterocycles with good pharmacological profiles and extensive biological activities . Nevertheless, direct de novo synthesis of fully substituted thiazoles with dicarbonyl functional groups from easily available materials remains challenging, because it is difficult to synthesize heterocycles in situ while achieving their carbonylation in one reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally thiazoles are prepared by Hantzsch thiazole synthesis involving α-halo ketone and thioamides . Considering the importance of green chemistry and the requirement for better alternative methods for the synthesis of substituted thiazoles, over the years, many methods have been developed using the combinations of different starting materials as well as catalysts and reaction conditions . Comparison of a few recent methods with our present method for the synthesis of substituted thiazoles is shown in Scheme .…”
Section: Introductionmentioning
confidence: 99%